The Association between Malnutrition and Physical Performance in Older Adults: A Systematic Review and Meta-Analysis of Observational Studies. Issue 4 (29th January 2022) - Kramer, Charlotte S; Groenendijk, Inge; Beers, Sonja; Wijnen, Hugo H; van de Rest, Ondine; de Groot, Lisette C P G M
Abstract: In recent years the focus of healthcare and nutritional science in older adults has shifted from mortality towards physical performance and quality of life. The aim of this review was to summarize observational studies on physical performance in malnourished (MN) or at risk of malnutrition (RMN) older adults compared with well-nourished (WN) older adults. Eligible studies had to report on nutritional status and objectively measured physical performance in older adults (≥60 y). MN or RMN groups had to be compared with a WN group, measured with a validated nutrition screener. Ovid Medline and Web of Science were searched until 13 November, 2020. Study quality was scored using a modified Newcastle–Ottawa Scale (NOS). Results were analyzed by meta-analysis when possible, or narratively reviewed otherwise. Forty-five studies (16, 911 participants in total) were included from studies in outpatient clinics ( n = 6), nursing homes ( n = 3), community-dwelling older adults ( n = 20), hospitalized patients ( n = 15), or a combination ( n = 1). Studies used 11 different screeners of malnutrition, and 8 types of physical performance measures. Meta-analysis showed that compared with MN, WN groups had better hand grip strength (mean difference [MD] = 4.92 kg; 95% CI: 3.43, 6.41; P < 0.001; n = 23), faster gait speed (MD = 0.16 m/s; 95% CI: 0.05, 0.27; P = 0.0033; n = 7), performed faster on timed-up-and-go (MD = –5.94 s; 95% CI: –8.98, –2.89; P < 0.001; n = 8), and scored 1.2 more short physical performance battery points (95% CI: 1.32, 2.73; P < 0.001; n = 6). Results were less pronounced when compared with RMN. Narratively, all studies showed an association for knee extension strength, 6-min walking test, and multicomponent tests, except for the chair stand test. Study limitations include no studies scoring "good" on NOS, lack of confounder adjustment, and high heterogeneity. Overall, evidence from cross-sectional studies indicate an association between malnutrition and worse physical performance in older adults. This study is registered in PROSPERO as CRD42020192893. Abstract : Intervention studies on malnutrition and physical performance show mixed results. This review looked at the underlying assumption and shows that malnourished populations have decreased physical performance compared with well-nourished populations.